2020
DOI: 10.1108/ssmt-11-2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of inkjet printed capacitor layers in various technological conditions

Abstract: Purpose The purpose of this paper is to analyze the individual steps during the printing of capacitor structures. The method of substrate preparation, the obtained roughness of conductive and dielectric layers are examined. Moreover, the capacitances of the obtained capacitors were examined. Design/methodology/approach Surface roughne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Regardless of which ink-jet printing process with any conductive material is considered as the functional phase of the ink, it consists of three basic steps: substrate preparation, printing, and sintering [31], as shown in figure 4.…”
Section: Materials and Ink-jet Printing Processmentioning
confidence: 99%
“…Regardless of which ink-jet printing process with any conductive material is considered as the functional phase of the ink, it consists of three basic steps: substrate preparation, printing, and sintering [31], as shown in figure 4.…”
Section: Materials and Ink-jet Printing Processmentioning
confidence: 99%
“…Zikulnig et al [15] also used the Van der Pauw method to determine the resistance of printed silver patterns on paper substrates. In the literature, some examples of publications can be found that describe different issues related to inkjet printing, such as individual drops [16,17], individual layers [18], and modelling [19,20]; the results of studies describe the influence of different factors (e.g., wettability) [21] to indicate the possibility of printing structures with fewer defects. For example, Lorwongtragool et al studied the morphology of printed lines [22].…”
Section: Introductionmentioning
confidence: 99%